Evolving growth hormone deficiency: proof of concept - Chimatapu, Sri Nikhita; Sethuram, Swathi; Samuels, Julie G.; Klomhaus, Alexandra; Mintz, Cassie; Savage, Martin O.; Rapaport, Robert (Frontiers in Endocrinology, 2024)
We present the evolution of GHD in adolescent males with persistent growth failure, in whom the diagnosis was established after a second GH stimulation test (GST).We performed a retrospective chart review of children who presented for short stature (height less < 2SD for mean/ mid-parental height) and/or growth failure (sustained growth velocity < 0 SD) to pediatric endocrinology at Mount Sinai Kravis Children's Hospital, New York and who had 2 GSTs. Data collected from electronic medical records were analyzed using SPSS v28.0 RESULTS: Of 53 patients included, 42 were males. Average GH peak on initial GST was 15.48 ± 4.92 ng/ml, at 10.07 ± 2.65 years, mean height -1.68 ± 0.56SD(28% had <2SD), IGF-1 -1.00 ± 0.88SD. After 2.23 ± 1.22 years, at 12.04 ± 2.41years, height SDs decreased to -1.82 ± 0.63SD and IGF-1 was -1.08 ± 0.84SD. At repeat GST, average GH peak was 7.59 ± 2.12 ng/dL, with 36% ≤7 ng/dl and 32% in puberty. 12 males reached adult height of 0.08 ± 0.69 SD with a mean height gain of 1.83 ± 0.56SD(p<0.005), IGF-1 of -1.15 ± 0.81SD after 4.64 ± 1.4 years of GH.We offer evidence for EGHDEvolving Growth Hormone Deficiency (EGHD) through repeat GST in children with persistent growth slowdown, even with pubertal progression; emphasizing the need for careful longitudinal follow-up to make accurate diagnosis.